Developing an ICF Core Set for adults with cerebral palsy: A Global expert survey of relevant functions and contextual factors - Chonnanid Limsakul; Suzie Noten; Melissa Selb; Henk J. Stam; Wilma M.A. van der Slot; Marij E. Roebroeck (Medical Journals Sweden, 2020)
Objective: To identify areas of functioning in adults with cerebral palsy that are considered relevant by experts, in order to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for adults with cerebral palsy. Participants: Experts from various professional backgrounds worldwide who had experience working with adults with cerebral palsy for ≥2 years and were able to complete the survey in the English language. Methods: A cross-sectional study using an international internet-based survey. The experts were asked to address relevant areas of functioning in adults with cerebral palsy. These areas of functioning were then linked to the ICF and the frequencies analysed. Results: A total of 126 experts from 32 countries completed the survey. From the responses, 217 unique second-level ICF categories were identified. The three most frequently mentioned categories were "design, construction and building products and technology of buildings for public use (e150, 77%) and private use" (e155, 67%), followed by "sensation of pain" (b280, 62%). Conclusion: The broad diversity of ICF categories reported by the experts emphasize the known heterogeneity of cerebral palsy and the variety of func-tioning in adulthood. They also reported on many environmental factors, illustrating the importance of person-environment interactions. These findings provide information about relevant issues for use in developing an ICF Core Set for adults with cerebral palsy.